Evaluation of the quality of life of lupus erythematosus patients with cutaneous lesions in Japan. (January 2014) - Ishiguro, M; Hashizume, H; Ikeda, T; Yamamoto, Y; Furukawa, F
The quality of life (QOL) of lupus erythematosus (LE) patients with skin manifestations is impaired, but little is known about Japanese patients. We assessed whether the skin symptoms in LE are associated with the QOL using the Japanese versions of the Skindex-29 and Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). In all, 54 LE patients with cutaneous lesions completed the Japanese version of the Skindex-29, and physicians assessed the severity of their eruptions using the CLASI before and after treatment. The QOL of the LE patients was better after the therapeutic intervention using the Skindex-29 questionnaire. We tested several factors for an independent association with the QOL. A significant risk factor for a poor QOL was a female gender in "Functioning" before treatment. In addition, a poor QOL tended to be correlated with a female gender in "Emotions" and older current age in "Symptoms" before treatment, and with a longer duration of SLE in "Functioning" after treatment. In the CLASI analysis, skin manifestation activity in the acute phase correlated with a poor emotional and functional QOL rather than a symptomatic QOL. To the best of our knowledge, this is the first report evaluating the QOL of Japanese LE patients, despite the small cohort.